The Effectiveness Of Using Text Messages Reminder On Adherence With Tuberculosis Patients: A Systematic Review - Barik, Ardila Lailatul; Indarwati, Retno; Sulistiawati, Sulistiawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Non-adherence is a factor that inhibits the completion of TB cases globally. Some studies suggest that the use of digital technology in the form of text message reminders can reduce the risk of non-adherence. The purpose of writing this article is to analyze the effectiveness of text message reminders on adherence to tuberculosis (TB) patients. The method in preparing this Systematic review is based on literature studies from various electronic databases, including Scopus, ScienceDirect, ProQuest, and Sage by conducting a comprehensive review using the PRISMA guidelines. The keywords used are "Text Messaging" AND "medication adherence" AND "tuberculosis". There are 11 original articles with 9 articles using the Randomized Control Trials (RCTs) research method and 2 articles using the Quasy-experimental method that fits the inclusion criteria. The use of text message reminder interventions is effective and can be used as an optional method of increasing adherence to TB patients.